High salivary levels of JP2 genotype of Aggregatibacter actinomycetemcomitans is associated with clinical attachment loss in Moroccan adolescents - Ennibi, O.K.; Claesson, R.; Reddahi, S.; Kwamin, F.; Haubek, D.; Johansson, A. (Clinical and Experimental Dental Research, 2019)
It has previously been shown that the presence of Aggregatibacter actinomycetemcomitans in subgingival plaque is significantly associated with increased risk for clinical attachment loss. The highly leukotoxic JP2 genotype of this bacterium is frequently detected in adolescents with aggressive forms of periodontitis. The aims of the study were to quantify the levels of JP2 and non‐JP2 genotypes of A. actinomycetemcomitans in saliva of Moroccan adolescents with the JP2 genotype earlier detected in the subgingival plaque. The salivary concentrations of inflammatory proteins were quantified and linked to the clinical parameters and microbial findings. Finally, a mouth rinse with leukotoxin‐neutralizing effect was administrated and its effect on the levels the biomarkers and A. actinomycetemcomitans examined. The study population consisted of 22 adolescents that previously were found to be positive for the JP2 genotype in subgingival plaque. Periodontal registration and sampling of stimulated saliva was performed at baseline. A mouth rinse (active/placebo) was administrated, and saliva sampling repeated after 2 and 4 weeks rinse. The salivary levels of JP2 and non‐JP2 were analyzed by quantitative PCR and inflammatory proteins by ELISA. Both the JP2 and the non‐JP2 genotype were detected in all individuals with significantly higher levels of the non‐JP2. Enhanced levels of the JP2 genotype of A. actinomycetemcomitans was significantly correlated to the presence of attachment loss (≥3 mm). Salivary concentrations of inflammatory biomarkers did not correlate to periodontal condition or levels of A. actinomycetemcomitans. The use of active or placebo leukotoxin‐neutralizing mouth rinse did not significantly interfered with the levels of these biomarkers. Saliva is an excellent source for detection of A. actinomycetemcomitans on individual basis, and high levels of the JP2 genotype were significantly associated with the presence of clinical attachment loss.
Keywords: Aggregatibacter actinomycetemcomitans; Interleukin‐1β; JP2 genotype; Quantitative PCR; Saliva; Virulence blocking